Paedophagic cannibalism, resource partitioning, and ontogenetic habitat use in an invasive lizard. Issue 6 (2nd November 2018) - Van Kleeck, Melissa J.; Smith, Thomas A.H.; Holland, Brenden S.
Abstract : Various aspects of social structure can be important drivers of basic behavioral patterns, including dispersal, intraspecific niche partitioning, and resource utilization. Juvenile–adult interactions such as agonistic displays and paedophagic cannibalism can result in avoidance of adults by juveniles, and can influence community structure via shifts in ontogenetic habitat use patterns and juvenile dispersal. In this study, we examined the role of agonistic behavior in determining differences in habitat utilization between life stages in an ecologically damaging invasive lizard, Trioceros jacksonii xantholophus, in the Hawaiian Islands. We tested the hypothesis that intraspecific aggression by adults drives observed niche separation and juvenile dispersal. In the laboratory, we conducted paired conspecific trials to assess paedophagic behavior, and staged contests to assess aggression and response: 57% of adults consumed newborns when paired. In addition, juveniles fled further, faster, and more often in response to aggressive adult displays than from other juveniles. To assess the effect of antagonistic behaviors on juvenile movement and its potential role in and habitat shifts, we used radio-telemetry and exploited diet comparison to assess resource use in juveniles versus adults. Though our results suggested no significant difference in immature versus adult chameleon dispersal, juveniles were found to perch at significantly lower heights above ground, and exploited different prey types than did adults. These results suggest that resource partitioning is occurring, but the immature chameleons are sedentary as are the adults. Due to age-dependent habitat usage, our results suggest that T. j. xantholophus occupies a broader niche than previously recognized. These results highlight the importance of studies focused on patterns of behavior at different developmental stages of invasive species, which ultimately provide better information allowing prediction of ecological impacts and range expansion potential.